PENGARUH PENDIDIKAN DAN PELATIHAN TERHADAP PRODUKTIVITAS KERJA KARYAWAN BAGIAN PRODUKSI PADA PT. SEMEN BATURAJA (PERSERO) TBK PALEMBANG - Aliya, Sabeli; Tobari, Tobari (Graduate Program Magister Manajemen Pendidikan, 2019)
This study aimed at finding out how much the influence of education and training on the productivity of production employees at PT. Semen Baturaja (Persero) Tbk Palembang; in a manner partially and simultaneously. The research method used was descriptive quantitative. The data analysis technique used is multiple regression analysis. The sample designation technique was carried out by purposive sampling. The conclusions of this study are (1) Education Variables have no significant effect on the work productivity of production section employees. (2) Training variables proved to have a positive effect on Employee productivity at PT. Semen Baturaja (Persero) Tbk Palembang. (3) If the two variables are tested simultaneously education and training have a significant influence on employee work productivity. (4) The results show that education and training affect work productivity by 22.1%, and the remaining 77.9% is influenced by other variables. Based on the results of the calculation shows the multiple linear regression equation, namely: Y = 2.281 + 0.247 + 0.478. The regression coefficient is positive, so it can be said that the direction of influence of education and training is a positive influence.